Pemberdayaan Masyarakat dalam Pengelolaan Air Bersih Berkelanjutan melalui Program Air Minum Muhammadiyah (PAMMU) di Desa Kadipiro, Sambirejo, Sragen - Jumadi, Jumadi; Priyana, Yuli; Danardono, Danardono; Umrotun, Umrotun (Penerbit Widina, Widina Media Utama, 2025)
This community service program aims to improve sustainable access to clean water and strengthen community independence through the Muhammadiyah Drinking Water Program (PAMMU) in Kadipiro Village, Sambirejo District, Sragen Regency. The method employed was Participatory Action Research (PAR), which emphasizes the active involvement of the community at every stage of the program. The activities began with problem identification and local potential mapping through Focus Group Discussions (FGDs), followed by the participatory development of a roadmap and action plan, as well as technical training and institutional strengthening for the community-based water management organization. The action phase was reinforced with collective reflection and participatory evaluation, resulting in enhanced managerial capacity, the establishment of a participatory institutional structure, and the creation of a local drinking water brand, “Enbia.” The outcomes demonstrated significant improvements in knowledge, hygiene and sanitation practices, and community-based institutional management of clean water. Despite challenges such as limited funding and infrastructure, the PAR model proved effective in fostering multi-stakeholder collaboration, enhancing community self-reliance, and ensuring the sustainability of clean water management. This model holds potential for replication in other villages facing similar challenges.ABSTRAKKegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan akses air bersih berkelanjutan dan memperkuat kemandirian masyarakat melalui Program Air Minum Muhammadiyah (PAMMU) di Desa Kadipiro, Kecamatan Sambirejo, Kabupaten Sragen. Metode yang digunakan adalah Participatory Action Research (PAR), yang menekankan keterlibatan aktif masyarakat dalam setiap tahapan. Program dimulai dengan identifikasi masalah dan potensi lokal melalui Focus Group Discussion (FGD), dilanjutkan dengan penyusunan roadmap dan action plan secara partisipatif, serta pelatihan teknis dan pendampingan kelembagaan pengelola air bersih. Proses aksi ini diperkuat dengan refleksi dan evaluasi bersama, yang menghasilkan peningkatan kapasitas pengelola, terbentuknya kelembagaan partisipatif, serta lahirnya merek air minum lokal “Enbia”. Hasil pengabdian menunjukkan adanya perubahan signifikan pada aspek pengetahuan, perilaku hidup bersih dan sehat, serta pengelolaan kelembagaan air berbasis masyarakat. Meskipun masih terdapat tantangan pendanaan dan keterbatasan infrastruktur, model PAR ini terbukti mampu memperkuat kolaborasi multipihak, meningkatkan kemandirian warga, serta mendukung keberlanjutan pengelolaan air bersih. Temuan ini dapat direplikasi di desa lain yang menghadapi permasalahan serupa.